2021
DOI: 10.3390/kidneydial1020014
|View full text |Cite
|
Sign up to set email alerts
|

Do Exercise, Physical Activity, Dietetic, or Combined Interventions Improve Body Weight in New Kidney Transplant Recipients? A Narrative Systematic Review and Meta-Analysis

Abstract: Weight gain within the first year of kidney transplantation is associated with adverse outcomes. This narrative systematic review and meta-analysis examines the effect of exercise, physical activity, dietary, and/or combined interventions on body weight and body mass index (BMI) within the first year of kidney transplantation. Seven databases were searched from January 1985 to April 2021 (Prospero ID: CRD42019140865), using a ‘Population, Intervention, Controls, Outcome’ (PICO) framework. The risk-of-bias was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The need for support to engage with online interventions is echoed in the few studies that explore PA and dietary combined interventions in new KTRs ( 15 ). Exit survey data from Serper et al ( 72 ) reported participants would have valued technical support and contact with the research team.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The need for support to engage with online interventions is echoed in the few studies that explore PA and dietary combined interventions in new KTRs ( 15 ). Exit survey data from Serper et al ( 72 ) reported participants would have valued technical support and contact with the research team.…”
Section: Discussionmentioning
confidence: 99%
“…They have also been associated with appetite stimulation and changes in nutrient partitioning that favor fat deposition ( 14 ). Therefore, interventions to address weight gain and modifiable risk factors such as physical activity and healthy eating behaviors are warranted ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst weight gain is a significant issue for new kidney transplant recipients, there is no recommended intervention designed to prevent adverse weight gain from occurring [27]. The systematic review and meta-analysis by Castle et al [28] Behavioural change techniques are recommended to facilitate physical activity and dietary interventions [29]. In this Special Issue, Leunis et al [30] explore physical activity behaviour in solid organ transplant recipients.…”
mentioning
confidence: 99%